1986
DOI: 10.1111/j.1365-2125.1986.tb02942.x
|View full text |Cite
|
Sign up to set email alerts
|

The effect of oral verapamil therapy on antipyrine clearance.

Abstract: The influence of chronic verapamil treatment on antipyrine elimination was studied in eight angina patients. Antipyrine half-life (mean ± s.d.) was 13.1 ± 1.15 h at the start of therapy and 16.6 ± 3.05 h (P < 0.05) during chronic oral administration of verapamil (80 -120 mg four or three times daily for 4 to 7 months). There was a significant decrease in antipyrine clearance (mean ± s.d, 43.2 ± 16.8 ml min-' vs 28.7 ± 16.6 ml min-', P < 0.01) while the change of distribution volume was insignificant. Verapamil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
9
0

Year Published

1987
1987
1993
1993

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 19 publications
(23 reference statements)
0
9
0
Order By: Relevance
“…Alternatively any inhibitory effect on parent drug metabolism may be offset by an increase in autoinduction during chronic CBZ therapy. Interestingly, VPA did not inhibit antipyrine metabolism significantly at relatively high concentrations of the drug unlike other enzyme inhibiting drugs that modify CBZ disposition, such as cimetidine (Macphee et al, 1984) and verapamil (Rumiantsev et al, 1986).…”
Section: Analysesmentioning
confidence: 91%
“…Alternatively any inhibitory effect on parent drug metabolism may be offset by an increase in autoinduction during chronic CBZ therapy. Interestingly, VPA did not inhibit antipyrine metabolism significantly at relatively high concentrations of the drug unlike other enzyme inhibiting drugs that modify CBZ disposition, such as cimetidine (Macphee et al, 1984) and verapamil (Rumiantsev et al, 1986).…”
Section: Analysesmentioning
confidence: 91%
“…Verapamil has been shown to increase the steady-state accumulation of CQ by CQ-resistant P. falciparum, and it was suggested that this effect was due to the inhibition of CQ efflux (18 The question remains as to whether the reversal of resistance produced by verapamil is related in any way to the mechanism involved with cimetidine. It is noteworthy that verapamil as well as cimetidine and metyrapone has been shown to be an inhibitor of the cyt P-450 superfamily of enzymes (22,24,30). These inhibitors are all selective for the isozymes of cyt P450 that they inhibit (3), a fact that raises the possibility that the differences observed in the modulatory effects of the drugs tested may reflect differences in the relative affinities of specific isozymes of cyt P450: i.e., Km for verapamil c that for cimetidine <<< that for metyrapone.…”
Section: Discussionmentioning
confidence: 99%
“…Verapamil has been demonstrated to inhibit the clearances of antipyrine (Bauer et al, 1986;Rumiantsev et al, 1986) and carbamazepine (Macphee et al, 1986) in man. A case report suggests that verapamil may also inhibit theophylline clearance (Burnakis et al, 1983).…”
Section: Introductionmentioning
confidence: 99%